Advanced multi-domain method for multiphase flow interaction with Lagrangian structural meshes. (15th July 2019) - Kanarska, Yuliya; Schofield, Samuel; Dunn, Timothy; Liu, Benjamin; Noble, Charles
Abstract: Multiphase flow with particulates has emerged as a topic of fundamental fluid and continuum mechanics interest in many applications including national security applications. For more efficient simulation workflows, the utilization of a separate background multiphase flow mesh and foreground Lagrangian structural meshes is greatly beneficial. We propose a multi-domain coupling method for multiphase Godunov compressible high-speed flow interacting with an ALE structure on a different mesh. Along with cell centered updates in ghost points similar to ghost fluid methods we use additional modifications of the solid states at faces in such a way that resulting solution of the Riemann problem at each face satisfies the boundary interface conditions. Due to variation in targets and potentially dense particulate phases, the embedded grid coupling methodology needs to be stable across a wide range of fluid/structure density ratios as well as both dense and dilute particle regimes. We are developing multiphase extensions of the Banks, et. al. (2011) interface conditions that are appropriate for the wide range of multi-phase flow conditions. Several examples demonstrate applicability of the method for multiphase flow interaction with dynamic deformable Lagrangian structural meshes.